2013
DOI: 10.1002/ccd.24901
|View full text |Cite
|
Sign up to set email alerts
|

Provisional side branch‐stenting for coronary bifurcation lesions

Abstract: Together, contemporary techniques and newer generation DES appear to improve outcomes and are both recommended for widespread uptake in patients undergoing provisional SB stenting for coronary bifurcation lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Furthermore, diameters (balloon/vessel ratio) and patterns of balloons during FKBI (as short overlapping as possible in the MV) were not fixed in the previous studies, 1 5 which also influences the short- and long-term results. 14 Bench tests 14 , 15 and clinical analysis 16 have addressed the importance of the proximal optimization technique after FKBI to improve immediate and 1-year results; the technique was proposed before the start of either Nordic Bifurcation study 5 or the DKCRUSH-II study. Consequently, the routine use of the proximal optimization technique should be recommended in further clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, diameters (balloon/vessel ratio) and patterns of balloons during FKBI (as short overlapping as possible in the MV) were not fixed in the previous studies, 1 5 which also influences the short- and long-term results. 14 Bench tests 14 , 15 and clinical analysis 16 have addressed the importance of the proximal optimization technique after FKBI to improve immediate and 1-year results; the technique was proposed before the start of either Nordic Bifurcation study 5 or the DKCRUSH-II study. Consequently, the routine use of the proximal optimization technique should be recommended in further clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“… 26) It also improves a proximal MV stent apposition and eccentricity. 27) According to the Murray's law, POT is mandatory when SB size large than 2.3 mm, for the discrepancy between PV and MV size is mostly larger than 1.0 mm. The subgroup analysis of COBIS II registry showed that the POT significantly reduced the restenosis rate in MV in the bifurcation lesions with SB size ≥2.5 mm in core-lab quantitative coronary angiography (unpublished data).…”
Section: Mechanisms Of Sb Compromise and How To Avoid Itmentioning
confidence: 99%
“…The clinical effects of renal denervation could already be detectable one month after the procedure , but it often takes several weeks to months before reaching peak effectiveness suggesting that a slowly progressive resetting of sympathetic neural regulation occurs [4][5][6]9,10,16,19 . Therefore, these deadlines are advisable to collect data of home BP and to check office BP, ambulatory blood pressure monitoring (ABPM) is also recommended.…”
Section: High-volume Interventional Radiology/cardiology Experiencementioning
confidence: 99%